Implementasi Manajemen Kurikulum Terpadu Di Madrasah Tsanawiyah - Khamim Syaibani; M Afif Zamroni (Pedir Research Institute, 2021)
Abstract: The purpose of this article is to discuss the implementation of integrated curriculum management in improving student competence in MTs. Al-Amin Islamic Boarding School Mojokerto. This article uses a descriptive qualitative approach. Sources of data and documents obtained through interviews, observation, and documentation. The study was conducted from January to May 2021. The findings of this article are 1) implementation of integrated curriculum management in improving student competence at Mts Mojokerto applying the formulation of curriculum content or content adjusted to Content Standards and Graduate Competency Standards so that correlation occurs between groups of general subjects of religion and language ,2) The structure of an integrated curriculum based on the needs of students in the short, medium and long term, 3) Evaluation as a measure of the level of students' abilities in improving student competencies. The theoretical findings of this study indicate that increasing student competence from educational institutions can be carried out with an effective and efficient curriculum management process in accordance with the school's vision and mission.